A review on computer-aided design and manufacturing of patient-specific maxillofacial implants. (2nd April 2020) - Memon, Afaque Rafique; Wang, Enpeng; Hu, Junlei; Egger, Jan; Chen, Xiaojun
ABSTRACT: Introduction : Various prefabricated maxillofacial implants are used in the clinical routine for the surgical treatment of patients. In addition to these prefabricated implants, customized CAD/CAM implants become increasingly important for a more precise replacement of damaged anatomical structures. This paper reviews the design and manufacturing of patient-specific implants for the maxillofacial area. Areas covered : The contribution of this publication is to give a state-of-the-art overview in the usage of customized facial implants. Moreover, it provides future perspectives, including 3D printing technologies, for the manufacturing of patient-individual facial implants that are based on patient's data acquisitions, like Computed Tomography (CT) or Magnetic Resonance Imaging (MRI). Expert opinion : The main target of this review is to present various designing software and 3D manufacturing technologies that have been applied to fabricate facial implants. In doing so, different CAD designing software's are discussed, which are based on various methods and have been implemented and evaluated by researchers. Finally, recent 3D printing technologies that have been applied to manufacture patient-individual implants will be introduced and discussed.